PERBEDAAN PERILAKU INVESTOR TERHADAP PENGUMUMAN PERUBAHAN PERINGKAT OBLIGASI PERUSAHAAN ASING VERSUS DOMESTIK - , IRDHA YUSRA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research is to examine differences behavior investors to bond rating changes in foreign and domestic companies. The event date is the time when PT Pefindo as a rating agency in Indonesia announce the changes of bond rating during 2002-2011. Event study method is used to analyze investor reaction to bond rating changes announcement. The samples are taken by purposive sampling method and the results are 89 observation, 51 upgrade and 8 downgrade for foreign companies, 15 upgrade and 16 downgrade for domestic companies. Market model used to calculate whether there is any abnormal return. Event windows are 21 days which 10 days before the rating announcement, the day of rating announcement, and 10 days after the rating announcement. The variables is average abnormal return. Generally, the were positive abnormal return at bond rating upgrade announcement and there were negative abnormal return at bond rating downgrade announcement. The result is Indonesian Capital Market, especially Indonesian Stock Exchange significantly react to bond rating upgrade and downgrade, for both categories of foreign and domestic companies. This results indicates that investors react positively to the announcement of the change of bond rating companies foreign and domestic. This research also find different response from investors, where the reaction of investors to changes of bond rating from domestic companies higher than to changes of bond rating from foreign companies.